Characterization of mesenchymal progenitor cells in crown and root pulp from human mesiodentes. (8th April 2014) - Sato, M; Toriumi, T; Watanabe, N; Watanabe, E; Akita, D; Mashimo, T; Akiyama, Y; Isokawa, K; Shirakawa, T; Honda, MJ
Abstract : Objective: Mesiodentes are usually found in the central position of the upper or lower jaw as supernumerary teeth. Here, we obtained 10 mesiodentes and three permanent teeth (PT) and separated the dental pulp (DP) from these into crown and root portions. We then characterized and compared the isolated crown portion‐derived cells (crown cells) with root portion‐derived cells (root cells) using a range of in vitro assays. Materials and methods: Crown cells and root cells were examined for cell surface marker expression, colony‐forming unit‐fibroblast (CFU‐F), cell proliferation, cell cycle characteristics and markers, and osteogenic and adipogenic differentiation. Results: The proportion of CD105‐positive cells (CD105 + cells) in the crown cells vs the root cells varied among the mesiodentes, but not among the PT. When there were more CD105 + cells in the root cells than in the crown cells, the root cells showed higher CFU‐F, proliferation capacity, and osteogenic differentiation capacity. In contrast, when the crown cells contained more CD105 + cells than the root cells, the crown cells showed the higher CFU‐F, proliferation capacity, and osteogenic differentiation capacity. In addition, the sorted CD105 + cells showed higher CFU‐F and proliferation capacity than the sorted CD105 − cells. Conclusion: These results indicated that proportion of CD105 + cells is an effective means of characterizing DP‐derived cells in mesiodentes.